Applications of α,β-Symmetrical Functions on a Certain Class of Spirallike Functions - Aljazi Alkhammash; Fuad Alsarari (Journal of Function Spaces)
In this note, we use the notions of α,β-symmetrical, generalized Janowski-type and spirallike functions to define a new class Sα,βλN,M,μ defined in the open unit disk. In particular, we obtain a structural formula, a representation theorem, Marx-Strohacker inequality. Our results continue to hold the covering and distortion properties.